Democracy and Development Nexus: Assessing President Tinubu’s Renewed Hope Agenda and Welfare of Nigerians, 2023-2025 - Azeez, Ademola; Oluseyi , Olaleye (Journal of Contemporary International Relations and Diplomacy, 2026)
Nigeria’s experiment with democracy has always carried both longing and tension, a nation reaching for development with one hand while steadying its fragile democratic foundations with the other. This study revisits that delicate dance by examining President Bola Ahmed Tinubu’s Renewed Hope Agenda (2023-2025) as a contemporary lens into the democracy-development nexus. Grounded in a mixed-methods design and inspired by a pragmatic research philosophy, the study weaves modernization theory, the democratic-advantage thesis, Rudebeck’s vision of substantial democracy, and Dudley Seers’ human-centered development standards into a single analytical tapestry. Using empirical indicators from national and international datasets, complemented by qualitative insights from policy actors, civil society voices, and lived experiences of citizens, the study reveals an unfolding narrative of reform, sacrifice, and fragile possibility. The early reforms, notably subsidy removal and exchange-rate liberalisation created economic turbulence and widespread distress. Yet beneath the hardship lie subtle signs of rebalancing, institutional correction, and cautious recovery. The findings show that while technical reforms may stabilise macroeconomic foundations, they do not automatically translate into tangible welfare gains. Development under democracy must be more than a policy agenda; it must be a lived assurance, a people-centred promise. The Renewed Hope Agenda therefore stands at a crossroads: its legitimacy will depend not on boldness alone, but on whether democratic governance can turn sacrifice into shared progress, and policy ambition into human wellbeing